Evaluasi Sistem Informasi Akuntansi Penjualan Tunai Sebagai Alat Pengendalian Internal Pada CV Karya Abadi - Lis Lestari Sukartiningsih; Silvia Indrarini; Theresa Juliana Patricia Widiyono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to evaluate the cash sales accounting information system as an internal control tool at CV Karya Abadi. This type of research is a case study using field study and literature study data collection methods. Data collection techniques are observation, interviews and documentation. The analysis technique uses qualitative descriptive analysis. The problem in this research is the weakness of the cash sales accounting information system. This is proven by the dual function of the sales administration section which doubles as the accounting section, the documents and accounting records used are still incomplete. The cause of this problem is a lack of human resources and a lack of company understanding of the importance of a cash sales accounting information system. As a result, there was a delay in submitting cash sales information and errors occurred in recording cash sales, and the company experienced losses and lost its assets. The results of the analysis by separating functions in the accounting and sales administration sections, improving the organizational structure, adding documents in the form of warehouse cards, cash sales invoices and goods delivery letters as well as accounting records in the form of sales journals, cash receipts journals, as well as improving cash sales systems and procedures, then internal control can run effectively.